PHARMACOLOGICAL EVALUATION OF INFLORESCENSE OFAERVA PSEUDOTOMENTOSA BLATT . & HALLB. - agarwal, Sumit; Tomar, Atul Singh; Gupta, Mahesh Kumar; Kabra, Mahaveer Prasad; Gupta, Raman Bihari (Asian Journal of Pharmaceutical Research and Development, 2013)
World Health Organization (WHO) has defined herbal medicines as finished, labeled medicinal products that contain active ingredients, aerial or underground parts of the plant or other plant material or combinations. World Health Organization has set specific guidelines for the assessment of the safety, efficacy, and quality of herbal medicines. Aerva is a genus of plant in the family Amaranthaceae with about 167 species around Mediterranean, Asia and in the North America. The Aerva pseudotomentosa Blatt.& Hallb. is globally distributed in Pakistan and India. It is found from arid and semiarid region of Rajasthan state mainly in Jodhpur, Barmer, Bikaner, Churu, Jaiselmer, Jhunjhunu, Sikar and Shri Ganganagar districts and is commonly known as Bui, Buari. It is small, spiny, erect, undershrubs; more and less grandullar; branchess slander, terete, triate, glabrous. Leaves opposite, 1-3 foliate; petioles very variable in length, from 3 - 30 mm long, deeply striate, very slender; stipules 2 pairs of sharp slender thorns, sometimes exceeding 12 mm in length; leaflet linear, acute, and sessile or with very short petiolules. The ethanolic extract of A. Pseudotomentosa in doses of 200 and 400 mg/kg significantly suppressed carrageenan-induced paw edema in rats 70.15% and 67.08% for PE while 44.89% and 60.29% for EE while Both ethanolic and acetone extracts of the plants were found to exhibit a dose dependent increase in latency time when compared with control. At 90 minutes, the percent inhibition of two different doses (200 and 400 mg/kg body weight) was 50.00% & 65.51% for ethanolic extract and 35.14% & 56.56% for acetone extract respectively.